Analysis of Sub-Sector Performance of Agriculture in Pekalongan Regency, 2013-2017 - Rahayu Mustika Wati; Oke Setiarso; Agus Arifin (EKO-REGIONAL, 2020)
This research is secondary data research in the agricultural sub-sectors, those are food crops, horticulture, plantations, animal husbandry, agriculture and hunting services, forestry and logging, and fisheries in Pekalongan Regency in 2013-2017. The purpose of this research is to analyze the classification of growth and the contribution of plantations sub-sector production. This research used analysis tools, they were Klassen Typology and Contribution Production of superior products in each district. The results of this research show growth classification consist of four quadrants: quadrant I that doesn’t have advanced agricultural sub-sectors. Quadrant II contained horticultural crops, forestry and logging, and fisheries, while in Quadrant III there were plantation crops, and in Quadrant IV there were food crops, livestock, and agricultural and hunting services. Pekalongan Regency has 19 districts, with 15 products of plantation crop. Contribution Production shows that Paninggaran District had the highest contribution of plantation crops in the Pekalongan Regency.Keywords: Agriculture Sub Sector, Growth Classification, Contribution